Discontinuation of fucose therapy in LADII causes rapid loss of selectin ligands and rise of leukocyte counts. - Lühn, K; Marquardt, T; Harms, E; Vestweber, D (2001)
Leukocyte adhesion deficiency type II (LADII) is a rare inherited disorder of fucose metabolism. Patients with LADII lack fucosylated glycoconjugates, including the carbohydrate ligands of the selectins, leading to an immunodeficiency caused by the lack of selectin-mediated leukocyte-endothelial interactions. A simple and effective therapy has recently been described for LADII, based on the administration of oral fucose. Parallel to this treatment the lack of E- and P-selectin ligands on neutrophils was corrected, and high peripheral neutrophil counts were reduced to normal levels. This study reports that discontinuation of this therapy leads to the complete loss of E-selectin ligands within 3 days and of P-selectin ligands within 7 days. Peripheral neutrophil counts increased parallel to the decrease of selectin ligands. Selectin ligands reappeared promptly after resumption of the fucose therapy, demonstrating a causal relationship between fucose treatment and selectin ligand expression and peripheral neutrophil counts.